Corporate strategy for Forever Wood Corporation - Roleda, Mary Ann (Animo Repository, 1999)
The builders woodworks industry is relatively young. It only started in the eighties when the wood manufacturing technology began to improve. Major product lines, to name a few are doors, doorjambs, window frames, parquet, and others. The industry output is mainly intended for export due to high prices of woodworks, especially doors. However, there are some companies that sell to the local market. Resource requirements used to manufacturer wooden joineries require big chunks of wood that is of high quality and free from physical imperfections. Timber is normally sourced from Luzon and Mindanao. However, when the government implemented the log ban many manufacturers of wooden joineries import timber from other countries such as Papua New Guinea and Malaysia. Other materials needed are glue, sandpaper, paint, and others, for finishing and packaging purposes. Companies engaged in this industry had to invest in equipment as well as highly skilled laborers to produce quality product intended for the export market. Recently, there are about 16 top produce quality product intended for the export market. Recently, there are about 16 top players but far, there has been no dominant force in the industry. There are temporary market leaders such as Matimco and Forever Wood but have not sustained market shares over a long period of time. The countrys top five export markets for builders woodworks are Japan, UKNI, USA, France and Taiwan for the five-year period 1994 to 1998. Total export value of the five countries amounted to USD 318, 679, 691 million that is equivalent to 89.27% of the total export market. Wooden doors accounted for 30.04% of the countrys export for the period 1994-1998. Forever Wood Corporation started business in the 1970s and the company had grown to be one of the largest sawn timber manufacturer and distributor in the Central Visayas and Luzon areas. Of late, they have ventured into the wood working operation catering to the export market and recently, the local building industry. It has established market relations with the European buyers and is currently planning to enter the US market by year 2000. When the Asia financial crisis incurred losses in its dollar denominated loans and financial expenses grew by 50%. Moreover, the company is also encountering internal problems related to organization, cash flow and liquidity due to account receivable, wastage and poor stock evolution. Likewise, production had been slow due to re-planning of the production process, availability of quality raw materials, breakdown of machinery and unsatisfied laborers. This causes irregular production schedule that resulted to low output of door products. Consequently, demand of export and local market was not met.